Anthropisation Et Dynamique Des Paysages En Pays Agonlin Au Bénin - Akpoyètè, Damase Hintchémè; Landeou, Rodrigue C.; Orékan, Vincent O. (European Scientific Journal, ESJ, 2018)
The temporal dynamics of landscapes in pays Agonlin zone of south Benin (West Africa) were studied through a diachronic analysis of three Landsat images (TM 1986, ETM 2000 et OLI TIR, 2015), supported by field visits. The results indicate that the forest cover was reduced from 35.46 % in 1986 to 9.97 % in 2016. This decrease of forest area went together with a loss of savannah area. On the other hand, agricultural areas increased up to 23.21% over the same period. Landscape pattern analysis by means of configuration metrics revealed a fragmentation of natural and seminatural vegetation by agricultural activities, leading to an aggregation of agricultural patches. As general trend, human activities and demographic growth have caused significant changes to the landscapes of the study region.